Pengaruh Kepemilikan Pemerintah dan Struktur Modal Terhadap Kinerja Perusahaan BUMN dengan Firm Size sebagai Variabel Moderasi - Widodo, Rochmat Agung; Arza, Fefri Indra; Fawziah, Intan Nurbaiti (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to determine the effect of government ownership and capital structure on firm performance with firm size as a moderating variable. Firm performance is the dependent variable, while government ownership and capital structure are independent variables. The moderating variable is firm size. Firm performance is measured by the return on asset ratio. Capital structure is measured by the debt to equity ratio. Government ownership is measured by the division of government shares by total shares. Firm size is measured by total assets. The data used are annual reports and financial statements of state-owned enterprises in Indonesia listed on the Indonesia Stock Exchange in 2019-2023, with a sample of 20 firm. Data analysis used purposive sampling and moderated linear regression. The results showed that government ownership had no effect on firm performance. Capital structure had a negative effect on company performance. firm size did not moderate the effect of government ownership on company performance. firm size did not moderate the effect of capital structure on company performance.